1990
DOI: 10.1002/j.1460-2075.1990.tb08101.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro splicing of mutually exclusive exons from the chicken beta-tropomyosin gene: role of the branch point location and very long pyrimidine stretch.

Abstract: The chicken beta‐tropomyosin gene contains 11 exons, two of which are spliced into mRNA only in skeletal muscle. One pair of alternative exons, 6A and 6B, is found in the middle of the gene; they are spliced in a mutually exclusive manner. The non‐muscle splice 6A‐7 is by far the predominant in vitro reaction in a HeLa cell nuclear extract. A minor product is the 6A‐6B splice, which is excluded in all tissues. This minor product results from the use of a branch point located 105 nt upstream of the 3′ end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 34 publications
5
80
0
1
Order By: Relevance
“…Up to now, attempts to develop in vitro splicing systems prepared from different cell types, which mimic the regulated splicing pattern of cellular genes observed in these cell types, have been rather disappointing (for review, see Latchman 1990). This was the case for the analyses of calcitonin/CGRP pre-mRNA splicing with nuclear extracts from HeLa and PC12 cells (Bovenberg et al 1988} and of rat or chicken B-tropomyosin substrates containing the two mutually exclusive exons and the adjacent exons (Helfman et al 1988;Goux-Pelletan et al 1990). With the latter substrates, the existence of secondary structure covering regions of the alternative exons might explain the inefficient specific splicing in vitro (Libri et al 1989, as demonstrated previously by Eperon et al (1988).…”
Section: Discussionmentioning
confidence: 85%
“…Up to now, attempts to develop in vitro splicing systems prepared from different cell types, which mimic the regulated splicing pattern of cellular genes observed in these cell types, have been rather disappointing (for review, see Latchman 1990). This was the case for the analyses of calcitonin/CGRP pre-mRNA splicing with nuclear extracts from HeLa and PC12 cells (Bovenberg et al 1988} and of rat or chicken B-tropomyosin substrates containing the two mutually exclusive exons and the adjacent exons (Helfman et al 1988;Goux-Pelletan et al 1990). With the latter substrates, the existence of secondary structure covering regions of the alternative exons might explain the inefficient specific splicing in vitro (Libri et al 1989, as demonstrated previously by Eperon et al (1988).…”
Section: Discussionmentioning
confidence: 85%
“…The molecular basis for this is the proximity of the 5'-splice site of exon 2 relative to the branchpoint used for exon 3, which is only 42 nucleotides apart. In contrast, this mechanism cannot explain the mutually exclusive use of exons 6 and 7 in the rat and chicken B-TM genes, because the 5'-splice site of exon 6 in these genes is located at least 136 nucleotides upstream of the branchpoints used for the skeletal muscle exon (Helfman et al 1989(Helfman et al , 1990Goux-Pelletan et al 1990). Thus, the distant branchpoints of the [3-TM genes in rat and chicken play a different role in alternative splicing.…”
Section: The Role Of Distant Branch Sites In Alternative Splice-site mentioning
confidence: 96%
“…cellular factors involved in regulated alternative splicing, but a number of features in the pre-mRNA have been implicated in alternative splice-site selection. These include the relative strengths of 5'-and 3'-splice sites (Zhuang et al 1987;Kuo et al 1991;Mullen et al 1991), intron size (Fu and Manley 1987), the pyrimidine content of a 3'-splice site (Fu et al 1988;Mullen et al 1991), the location of branchpoints (Gattoni et al 1988;Helfman and Ricci 1989;Goux-Pelletan et al 1990;Helfman et al 1990), multiple alternative branchpoints (Noble et al 1987(Noble et al , 1988Gattoni et al 1988;Helfman and Ricci 1989), branchpoint sequences (Reed and Maniatis 1988;Zhuang et al 1989;Mullen et al 1991 ), intron sequences between a 3'-splice site and upstream branchpoint Helfman et al 1990;Libri et al 1990), and exon sequences (Reed and Maniatis 1986;Mardon et al 1987;Somaseker and Mertz 1985;Helfman et al 1988;Cooper and Ordahl 1989;Hampson et al 1989;Streuli and Saito 1989;Black 1991;Libri et al 1990Libri et al , 1991.…”
mentioning
confidence: 99%
“…These results were confirmed by primer extension analysis of branched and debranched RNA substrates (data not shown). Although functional BPSs are usually located within 18-40 nucleotides upstream of the AG, there are cases in which lariat formation occurs farther upstream (Gattoni et al 1988;Helfman and Ricci 1989;Reed 1989;Goux-Pelletan et al 1990). In these cases, the branchpoint sequence is followed immediately by a pyrimidine stretch.…”
Section: Productive and Nonproductive Branchpointmentioning
confidence: 99%